HUBUNGAN DUKUNGAN SOSIAL TERHADAP ACADEMIC BURNOUT PADA MAHASISWA YANG KULIAH SAMBIL BEKERJA - Felisca Kauwer; Niken Widi Astuti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Students who run two roles as learner and worker often face significant pressure because must balance academic demands and work professionalism in time which is stimultaneous. The blend of this double burden can increase the risk of academic burnout, which is defines as condition where students experience condition of emotional exhaustion, depersonalization, and decrease in academic achievement. Presence of this double pressure, social support can become one factor that can reduce level of burnout. Therefore, this research aims to test the relationship of social support toward academic burnout on students who study while working. In this research got a total of 476 respondents consisting of 204 male and 272 female who are studying while working. Research method used is quantitative correlational non-experiment with non-probability sampling technique. This research uses measuring tool Maslach Burnout Inventory – Student Survey with Alpha Cronbach 0.843 and Multidimensional Scale of Perceived Social Support with Alpha Cronbach 0.963. Normality test has been done and got result of normal data distribution. In this research, have tested correlation by using Pearson correlation test method with value of r as big as -0.407 and value of p as big as < 0.001. This result shows presence of significant negative relationship between academic burnout with social support. Therefore, can be concluded academic burnout and social support have relatioship.